Bank credit applications and advancement recommendations in regards to sustainable buildings in Turkey - (:unkn) unknown (IGI Global, 2016)
There are a wide variety of buildings that have been distinguished from traditional buildings with respect to their design, construction and utilization processes. These buildings are widely named ranging from passive, green, ecological to sustainable and are also differentiated as an intended consequence of their economic, social and environmental advantages. Consequently, the development of well-defined financial mechanisms aimed at promoting to business and individuals as well as the adoption of incentives by the governments are very important. This chapter recommends the following with respect to addressing sustainable building issues; the initiation of legal and regulatory structures concerning finance of energy investments, increasing the aggregate magnitude of the private credit packages prepared with the cooperation of energy productive focused firms and banks, diversification of the financial products and services as regards sustainable buildings, improvement of maturity extensions and tax exemptions pertaining to sustainable building private credits. © 2016 by IGI Global. All rights reserved.